Influence of polymeric matrix on the physical and chemical properties of experimental composites - Flávia GONÇALVES; Leticia Cristina Cidreira BOARO; Caroline Lumi MIYAZAKI; Yoshio KAWANO; Roberto Ruggiero BRAGA (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Nowadays, the main reasons for replacement of resin-based composite restorations are fracture or problems with the integrity of their interface, such as marginal staining, microleakage, or secondary caries. The aim of the present study was to evaluate the influence of the organic matrix on polymerization stress (PS), degree of conversion (DC), elastic modulus (E), flexural strength (FS), Knoop hardness (KHN), sorption (SP), and solubility (SL). In order to obtain a material which combines better mechanical properties with lower PS, seven experimental composites were prepared using BisGMA to TEGDMA molar ratios of 2:8, 3:7, 4:6, 5:5, 6:4, 7:3 and 8:2 and 40% of silica. PS was obtained in a universal testing machine, using acrylic as bonding substrate. DC was determined using Fourier Transform Raman spectroscopy. E and FS were obtained by the three-point bending test. KHN was measured by a microindentation test using a load of 25 g for 30 s. SP and SL were assessed according to ISO 4049. The data were submitted to one-way ANOVA. The increase in BisGMA concentration resulted in the decrease of PS, DC, E, FS and KHN. However, it did not change the SP and SL values. FS, E and KHN showed a strong and direct relationship with the DC of the materials. The composite material with a BisGMA to TEGDMA molar ratio of 1:1 was the one with better mechanical properties and lower PS.